MAPPING DATA LITERATURE, TECHNOLOGY LITERATURE, AND HUMAN LITERATURE IN COOPERATIVE ECONOMIC EDUCATION STUDENTS IN THE ERA OF THE INDUSTRIAL REVOLUTION 4.0 - Nikensari, Sri Indah; Suparno; Putri, Yuanda Eka (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
This study aims to analyze the level of data literacy, technological literacy, and human literacy as new literacy initiated by the Ministry of Research, Education and Technology for Cooperative Economic Education Students,State University of Jakarta, class of 2017-2019. The population in this study were all students of the 2017-2019 Economic Education study program. This research is a descriptive study with a mix method approach.Data collection techniques in this study were in the form of tests and interviews. The results of the test scores will be converted into a scale of 100 and divided into three categories, namely, high/good (75-100), moderate/enough (56-75), and low (1-55). The results of this study indicate that the level of data literacy ability of UNJ Cooperative Economics Education students is still relatively moderate with a total average score of 56.39. Meanwhile, the level of technological literacy is in the high/good category with a total average score of 92.9. Furthermore, for the last literacy, human literacy is included in the moderate/enough category with a total average value of 74.41.